Training on preparation of balanced nutrition and healthy food creativity to increase nutrition intake of school children during the Covid-19 pandemic: - - Nurul Huda; Rismadefi Woferst; E. Erwin; Eka Febriyanti (Universitas Muhammadiyah Malang, 2023)
The school aged students are vulnerable people to have nutritional problems particularly in this Covid 19-Pandemic era. This pandemic put children on the risk of nutritional problems, both malnutrition and obesity. Mothers are the closest person who have important role in providing childlren's diet. Therefore, the purpose of this community service’s program is to increase the knowledge and attitude of mothers in providing menu that meets nutritional balance for school-age children. The target of the program was the women of Kualu village, Tambang district, Riau Province with school-age children. The method used in this program were the provision of nutrition education based through counseling/lectures, training and demonstration. The results of the program showed that the level of mother’s' knowledge increased to 10.37 and 19.88 points. Furthermore, the mothers' creativity in providing the balanced diet also improved. The training also stimulated mothers to find new menus which mainly ingredients come from surrounding environment that meet nutrions need among school aged children. Therefore, the nutrition education program has been proved effective in increasing mothers' knowledge and creativity. Hence this program can be used as an additional program in Posyandu to optimize children nutritional status.